The Determinants of Agglomeration Redux: Transportation, Trade, and Input-Output Linkages - Kristian Behrens; Mark Brown; Théophile Bougna (European Regional Science Association (ERSA), 2014)
We study the determinants of agglomeration of Canadian manufacturing industries from 1990 to 2009. In so doing, we revisit the seminal contribution by Rosenthal and Strange (2001, "The determinants of agglomeration", J Urban Econ 50(2), 191?229) using a long panel and continuous measures of localization. We pay particular attention to the role of transporation costs ? constructed using extensive Canadian trucking microdata ? international trade exposure, and input sharing ? constructed using micro-geographic location patterns of plants. We find that between 1990 and 2009, industry localization has persistently fallen. The average degree of localization decreased by 36% within 10km, by 22.6% within 100km, and by 11.3% within 500km. Declining localization is associated with import competition, particularly from low wage countries, increasing transportation costs and the spreading out of upstream input suppliers and downstream demand for intermediate inputs. While we find strong evidence of trade-driven changes in localization, we find less evidence for knowledge spillovers and labour market pooling as drivers in changes in localization.
Keywords: R12; R30; L11; 330